2014
DOI: 10.1007/s10120-014-0449-9
|View full text |Cite
|
Sign up to set email alerts
|

Gene copy number gain of EGFR is a poor prognostic biomarker in gastric cancer: evaluation of 855 patients with bright-field dual in situ hybridization (DISH) method

Abstract: Background EGFR overexpression is a prognostic biomarker and is expected to be a predictive biomarker for anti-EGFR therapies in gastric cancer. However, few studies have reported the clinical impact of EGFR gene copy number (GCN) and its correlation with EGFR overexpression. Methods We used dual in situ hybridization (DISH) to detect EGFR GCN and chromosome 7 centromere (CEN7) in a set of tissue microarrays representing 855 patients with gastric cancer. These data were compared with those of immunohistochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…22 The amplified EGFR is a worse factor in GC initiation, invasion and metastasis. 23 LAMC2 colocalizes with EGFR to phosphorylate EGFR and activates its downstream signaling ERK1/2. 12, 24 CD82 suppresses EGFR expression and phosphorylation in EGF- and HGF-dependent manner in Hepa1–6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…22 The amplified EGFR is a worse factor in GC initiation, invasion and metastasis. 23 LAMC2 colocalizes with EGFR to phosphorylate EGFR and activates its downstream signaling ERK1/2. 12, 24 CD82 suppresses EGFR expression and phosphorylation in EGF- and HGF-dependent manner in Hepa1–6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Another study based on 855 cases reported that gained EGFR gene copy can be found in 22.7% of GC patients, and it associates with poor disease outcome. 84 These data collectively demonstrate that EGFR CNV may be a valuable biomarker for GC.…”
Section: Chromosomementioning
confidence: 93%
“…In addition to NRG1 amplification, increased NRG1 GCN signals were also observed. Since there are no standardized guidelines for evaluation of NRG1 gene status, we used a cutoff value adapted from a previous study on EGFR in GC [24]; hence, NRG1 GCN gain was defined as the copy number of NRG1 per nucleus of ≥ 2.5 ( Fig. 3).…”
Section: Immunohistochemistrymentioning
confidence: 99%